An Individually Controlled Multitined Expandable Electrode Using Active Cannula‐Based Shape Morphing for On‐Demand Conformal Radiofrequency Ablation Lesions. (20th July 2022) - Chai, Zhiping; Lyu, Liangxiong; Pu, Menghao; Chen, Xianwen; Zhu, Jiaqi; Liang, Huageng; Ding, Han; Wu, Zhigang
Abstract : Radiofrequency Ablation In article number 2100262, Zhigang Wu and co‐workers introduce a radiofrequency ablation device that can morph the shape of its electrode on demand with diverse morphological appearances. It can conformally, accurately ablate irregular shaped tumors that are widely seen in clinical practice and minimize the damage to vital organs for better recovery of patients.